Pemanfaatan Kulit Ubi Jalar Ungu Dengan Lama Perendaman Bahan Sebagai Indikator Asam Basa Alternatif Dan Variasi Pelarut Yang Berbeda - Mahfudhi, Ali; , Dra. Aminah Asngad, M.Si (2017)
Acid-base indicator is an important tool in science learning practice of middle school. Ingredients from plants containing anthocyanin have the potential for the making of natural base acid indicators. Purple sweet potato rind higher anthocyanin content than the meat, so it can be used as a natural base acid indicator. This research aim to know purple sweet potato rind extract can be utilized as material of making natural acid acid indicator with solvent variations and long submersion of material. This study used a complete randomized design, with two treatment factors which is different solvent variations and long submersion of the material. Variations of solvent used 96% ethanol, 96% ethanol + vinegar and ethanol 96% + 3% citric acid and long submersion of the material for 23 hours, 24 hours and 25 hours. The parameters of this study include the color change of acid base indicator paper from purple sweet potato rind extract after submersion in acidic and alkaline solutions. The results showed that the acid base indicator paper from the purple sweet potato rind extract experienced a red brick change in acidic and green tea solution in the alkaline solution. The length submersion of the material did not give a significant effect on the color of the indicator paper.